What we want to publish in 2025 - Paranaiba, Adriano; D’Andrea, Fernando (MISES: Interdisciplinary Journal of Philosophy, Law and Economics, 2025)
This editorial presents a discussion by the editors of the Mises Journal on the scope and objectives of the journal for the year 2025, as well as the pertinent topics for publication. Finally, we provide important information about the process of submitting articles to the journal, discussing the main reasons for rejection of submitted articles and suggesting ways to reduce or eliminate such problems in manuscripts.